2018
DOI: 10.1152/ajpheart.00681.2017
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide inhibition restores endothelium-dependent dilatation in aging arteries by enhancing impaired adherens junctions

Abstract: Endothelium-dependent, nitric oxide-mediated dilatation is impaired in aging arteries. The dysfunction reflects increased production of reactive oxygen species (ROS), is reversed by inhibiting superoxide with superoxide dismutase (SOD) mimics, and is assumed to reflect superoxide-mediated inactivation of nitric oxide. However, the dysfunction also reflects Src-dependent degradation and loss of vascular-endothelial (VE)-cadherin from adherens junctions, resulting in a selective impairment in the ability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Actin microfilaments can interact with endothelial adhesion structures and cooperatively regulate the cell shape. F-actin is a major actin protein in the endothelium and it is remodeled in response to nanomaterial exposure, oxidative stress and tumor necrosis factor [15,36,37]. Actin is an important component of "stress fibers" [38] and is responsible for endothelial contraction, which may lead to widening of inter-endothelial junctional gap and failure of the endothelial barrier [39].…”
Section: Discussionmentioning
confidence: 99%
“…Actin microfilaments can interact with endothelial adhesion structures and cooperatively regulate the cell shape. F-actin is a major actin protein in the endothelium and it is remodeled in response to nanomaterial exposure, oxidative stress and tumor necrosis factor [15,36,37]. Actin is an important component of "stress fibers" [38] and is responsible for endothelial contraction, which may lead to widening of inter-endothelial junctional gap and failure of the endothelial barrier [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that thrombin increased the microvascular permeability by activating PAR1 pathway, which increased the activity of downstream protein kinases, such as p21‐activated kinase‐1 (PAK1) . Several lines of evidence also indicated that the phosphorylation of Src or PAK1 was involved in the degradation and loss of VE‐cadherin …”
Section: Introductionmentioning
confidence: 99%
“…19 Several lines of evidence also indicated that the phosphorylation of Src or PAK1 was involved in the degradation and loss of VE-cadherin. [22][23][24][25] In this study, we hypothesized that thrombin-induced hydrocephalus was related to the PAR1 signaling pathway which resulted in the decline of VE-cadherin in choroid plexuses. And this process may shed light on the formation of hydrocephalus after IVH.…”
mentioning
confidence: 99%
“…In the aging heart, ECs shift the expression from laminin β2 to β1 and thereby modulate cell-matrix adhesion, cell migration and EndoMT in an autocrine manner that may impair vessel integrity [169]. Endothelial integrity is further disturbed by the age-related increase in ROS in the vasculature that leads to a Src-dependent degradation and loss of vascular-endothelial (VE)-cadherin from adherens junctions which impairs the ability to amplify endothelial dilation [170].…”
Section: Endothelial Cells In the Aging Heartmentioning
confidence: 99%
“…This pro-fibrotic and pro-inflammatory environment can be permissive for En-doMT and hence contribute to pathophysiologic alterations of the arterial wall like neointima formation and atherosclerosis. Evidences are given by studies showing that aged arterial ECs reduce internalization but increase degradation of VE-cadherin [170,179]. Furthermore, aging arterial ECs reveal a prominent intimal fibrous lesion with expression of rigid proteins such as collagen and fibronectin.…”
Section: Endothelial Cells In the Aging Heartmentioning
confidence: 99%